Experimental Study on Benchmarking Performance of Natural Circulation Flap Valve in DHR-400 - YU Song, ZHOU Ping, CHENG Daoxi, ZHAI Weiming, MA Xiaoyao, LI Ruizhi, XING Mingdi, GAO Weilong, GE Guangyuan, ZHANG Xuefeng, QI Xiaoguang, CHAI Baohua (Yuanzineng kexue jishu)
The 400 MW deep pool-type low-temperature heating reactor (DHR-400) is a novel pool-type reactor, which is designed by China National Nuclear Corporation (CNNC). Due to the design of deep pool, the core outlet temperature and working pressure of DHR-400 are relatively high. Thus, DHR-400 has the advantages in district heating and seawater desalination. In the case of loss of flow accident (LOFA), the nature circulation is used to export the residual heat of the reactor core. The natural circulation flap valve is an important equipment in the decay heat removal system of DHR-400, which can rely on its mechanical structure to complete passive opening. Because the flap valve is installed on the side of the core barrel, a nature circulation loop between core and pool is formed during LOFA. Therefore, it is crucial to clarify whether the performance of natural circulation flap valve complies with the design requirement of DHR-400. In this paper, an experimental facility was designed and constructed to analysis the performance of the natural circulation flap valve. Based on the working conditions of the natural circulation flap valve in reactor, the closing and opening abilities of the flap valve, and the leakage flow rate of the valve sealing surface under different closing conditions were obtained. The experimental results show that the performance of natural circulation flap valves is influenced by jet flow and pressure difference. During the closing process of natural circulation flap valve, the jet flow is the main factor affecting its close. However, the pressure difference is the main factor affecting the opening performance of the flap valve in the opening process. When the natural circulation flap valve is closed depending on jet flow or pressure difference, its critical jet flow rate of closing is about 41.6 kg/s. However, the natural circulation flap valve cannot be closed only by pressure difference. When the natural circulation flap valve is opened depending on jet flow or pressure difference, its critical jet flow rate of opening is about 39.2 kg/s. The critical pressure difference of opening the natural circulation flap valve is about 0.87 kPa, which satisfies the opening conditions of the flap valve within the pressure difference range of 0.8-1.0 kPa. In addition, the leakage flow rate of the natural circulation flap valve under different closing conditions was also measured, it is found that the natural circulation flap valve has good sealing performance. The research provides the reference and data basis for the engineering design and optimization of natural circulation flap valve.